Kajian Kesehatan Dan Keselamatan Kerja Pada Pekerjaan Penyelidikan Tanah Dengan Metode Boring - Soeparyanto, Try Sugiarto; Nuhun, Ridwan Syah; Ari Santika, I Gusti Ngurah Kade; Saputra, Wijaya (Innovative: Journal Of Social Science Research, 2025)
The implementation of construction projects often involves a high risk of work accidents, especially in the early stages such as soil investigations. Soil drilling activities (boring) are one of the important methods in determining the condition of the soil to be built. However, this method also has a significant potential for danger if not managed properly. The purpose of this study was to evaluate the implementation of the occupational safety and health (OHS) management system during the implementation of soil investigations using the boring method. The analysis was carried out by identifying hazards, assessing the level of risk, and formulating appropriate control measures based on the HIRADC (Hazard Identification, Risk Assessment and Risk Control) approach. The results of the study indicate that the implementation of OHS in this work still needs to be improved, especially in terms of the use of personal protective equipment (PPE), workforce training, and routine supervision in the field. This study is expected to be a reference in improving occupational safety standards in the soil investigation sector.